Magid Glove and Safety Manufacturing Co. - Ward, John L., 1945-; Perricelli, Susan Gegnas (London : Kellogg School of Management, 2005)
The case examines the strategies and protocols used by the Cohen family members to run Magid Glove & Safety Manufacturing and how these strategies enabled the company to thrive and for the family members to come to an agreement about the future of the company.
Originally published in Ward, J. L., & Perricelli, S. G. (2005). Magid Glove and Safety Manufacturing Co. 5-404-760. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Magid Glove and Safety Manufacturing Co; Business planning